ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA DALAM MENYELESAIKAN SOAL HOTS BERDASARKAN TAKSONOMI SOLO - Auliyau Rohman; Luluk Faridah; Khafidhoh Nurul Aini (INSPIRAMATIKA, 2020)
This study discusses students' understanding of the completion of HOTS based on the SOLO taxonomy. When understanding the concepts of students being analyzed namely (1) restate the concept, (2) classify objects based on certain traits, (3) use and utilize and choose certain procedures or operations, (4) 5) provide examples and not examples of an concept, (6) developing the necessary or sufficient requirements of a concept, (7) applying a concept or logarithm in problem solving. The subjects of this study were 15 students of MTs Model A'isyatul Wahidah class VIII which were divided into 3 levels: unistructural, multistructural and relational. The questions given consist of 2 essay questions (descriptions) that meet HOTS indicators and concept understanding. From this test can be seen indicators of understanding the concept. Each data obtained was analyzed in a descriptive form.